2014
DOI: 10.1038/ajg.2013.402
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Thiopurines in Reducing the Need for Surgical Resection in Crohn's Disease: A Systematic Review and Meta-Analysis

Abstract: TP use is associated with a 40% lowered risk of surgical resection in patients with CD. Despite significant reductions in rates of surgical resection in patients with CD over the last 5 decades and increasing use of TPs, a large proportion of patients with CD still require resectional surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 38 publications
1
58
0
1
Order By: Relevance
“…Immunomodulators are effective maintenance medications and azathioprine has been shown to modestly lower the risk of surgery [23][24][25] . A recent meta-analysis showed a combined pooled HR of 0.59 for first intestinal resection with thiopurine use [26] . Therefore, selecting patients who are most likely to benefit from IM may change the surgical rate of patients with CD.…”
Section: Discussionmentioning
confidence: 99%
“…Immunomodulators are effective maintenance medications and azathioprine has been shown to modestly lower the risk of surgery [23][24][25] . A recent meta-analysis showed a combined pooled HR of 0.59 for first intestinal resection with thiopurine use [26] . Therefore, selecting patients who are most likely to benefit from IM may change the surgical rate of patients with CD.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a meta-analysis of unselected cohorts focused on the role of thiopurines in need of surgical resection. This analysis revealed that there was approximately 40% reduction in surgery rate in CD patients using thiopurines (HR 0.64, 95% CI 0.44-0.93) [16] .…”
Section: Impact Of Immunomodulatorsmentioning
confidence: 99%
“…Surgery was more common in men aged 17-40 years. Prior intestinal surgery was associated with a marked increase in risk of PAS, whilst neither early steroid use nor smoking was associated with an increased risk PAS [16,27]. These findings reflect a significant burden of perianal disease requiring surgery amongst patient with CD and clinicians need to be aware that a requirement for PAS may often precede the diagnosis of CD by months or years.…”
Section: Main Findingsmentioning
confidence: 90%